Covalently attached organic monolayers onto silicon carbide from 1-alkynes molecular structure and tribological properties - Pujari, Sidharam P (Langmuir : the ACS journal of surfaces and colloids, 2013)
In order to achieve improved tribological and wear properties at semiconductor interfaces, we have investigated the thermal grafting of both alkylated and fluorine-containing ((C(x)F(2x+1))-(CH2)n-) 1-alkynes and 1-alkenes onto silicon carbide (SiC). The resulting monolayers display static water contact angles up to 120°. The chemical composition of the covalently bound monolayers was studied by X-ray photoelectron spectroscopy (XPS), infrared reflection-absorption spectroscopy (IRRAS), and near-edge X-ray absorption fine structure (NEXAFS) spectroscopy. These techniques indicate the presence of acetal groups at the organic-inorganic interface of alkyne-modified SiC surfaces. The tribological properties of the resulting organic monolayers with fluorinated or nonfluorinated end groups were explored using atomic force microscopy (AFM). It was found that the fluorinated monolayers exhibit a significant reduction of adhesion forces, friction forces, and wear resistance compared with non-fluorinated molecular coatings and especially bare SiC substrates. The successful combination of hydrophobicity and excellent tribological properties makes these strongly bound, fluorinated monolayers promising candidates for application as a thin film coating in high-performance microelectronic devices